Studies on Divergence for Fibre Yield and its Contributing Traits in Tossa Jute (Corchorus olitorius L.) - Dudhane, A. S.; Mukherjee, Subhra; Das, Bimal; Sarkar, K. K. (International Journal of Bio-resource and Stress Management, 2023)
Jute Christened as The golden fibre is the second most important textile fibre next to cotton. A field experiment with thirty diverse genotypes of jute (Corchorous olitorius L.) was undertaken at the teaching farm of Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal. For evaluation of yield characters based on D2 analysis, 30 genotypes were grouped into eight clusters. Cluster I had highest number of genotypes (18) followed by cluster II while cluster III, cluster IV, cluster V and cluster VI accommodated 2 genotypes each whereas cluster VII and VIII included solitary genotype. Maximum inter cluster distance was observed between cluster VII and cluster VIII and closely followed by VI and VII, while the minimum inter cluster distance were observed between cluster II and cluster III. Dry fibre weight per plant-1 followed by dry stick weight per plant-1 was the maximum contributors to total genetic divergence.